Factors contributing resistance to change in new organizational structure at Pejabat Tanah Daerah Segamat / Siti Radziah Mahfob - Mahfob, Siti Radziah (Faculty of Business and Management, 2014)
This study is proposed to identify the relationship between factors ofresistance to change to new organizational structure. The problem of this study is to identify factors that contribute to people resist changing towards new organizational structure change at "Pejabat Tanah Daerah Segamat". First, to identify the relationship between fear of unknown and new organizational structure change that implemented at "Pejabat Tanah Daerah Segamat". Second, to examine the relationship between loss of control and new organizational structure change that implemented at "Pejabat Tanah Daerah Segamat". Thirdly, to identify relationship between lack of confidence and new organizational structure change that implemented at "Pejabat Tanah Daerah Segamat". Fourth, to find the relationship between fear of taking risk and new organizational structure change that implemented at "Pejabat Tanah Daerah Segamat". Lastly, to identify how much those factors contributing toward resistance to change in new organizational structure at "Pejabat Tanah Daerah Segamat". The study involved 100 staffs from Federal Land Property Section, Research and Development Section, Land Intake Section and Human Resource Unit at "Pejabat Tanah Daerah Segamat". The research design for this research is quantitative which correlational study. Questionnaires were designed to gain information from the staff and have 28 questions that consists (3) three parts (Part A, B and C). Part A comprised the respondent's demographic information which are consists 6 questions. Part B comprised factors resistance to change which are fear of unknown consists 4 questions, loss of control consists 4 questions, lack of confidence consists 5 questions and fear oftaking risk consists of5 questions. Part C has 4 questions which are about organizational structure.